Evaluasi Buku Ajar Bahasa Arab Kelas X Madrasah Aliyah: Pendekatan Saintifik Kurikulum 2013 - Riham Lailatul Wachdah (Al-Ma‘rifah, 2020)
This study aims to evaluate Arabic teaching materials in Islamic High School (Madrasah Aliyah). The purpose of this evaluation is to find out the quality of Arabic textbooks for  class X based on the 2013 curriculum, published by the Ministry of Religious Affairs Republik Indonesia in 2014. The 2013 curriculum is a curriculum based on character and competence that requires children to be active in learning. The Arabic language textbooks are evaluated using a scientific approach to know the quality. In this study, the author uses descriptive qualitative methods, namely by emphasizing the aspect of understanding quality in depth to a problem and the results are not in the form of numbers, then systematically describing the facts and characteristics of the objects and subjects studied appropriately. The evaluation results of this teaching material show that from the aspect of presentation it has been systematic, coherent, consistent, and balanced between the chapters. From the aspect of supporting the dish, it does not contain a complete list of supporters. What's more, the connection of sentences is rather complicated. Meanwhile, from the linguistic aspect, there are still some misconceptions, especially in the use of alif and hamzah.